بعض المتغيرات الدموية والكولسترول لدى عينة من العاملين في محطات تعبئة الوقود في مدينة العمارة : العراق - صيهود علي عبدالله (University of Thi-Qar Journal of Science, 2014)
The present study included (90) males of gas stations laborers aged between ( 16- 60 years). They all subjected to estimation of hemoglobin concentration and total serum cholesterol , red blood and white blood cells count. 30 nonworking normal males from the same ages were elected as a control group and subjected to the same previous tests.The results showed decreasing in hemoglobin concentration ( p=0.021) concomitant decreasing of total serum cholesterol (p=0.036) in gas station workers in compare with control group. Also significant decreasing in red and white blood counts were noticed ( P< 0.001 ) in gas stations workers. It was also found that the previous parameters varies according to the period length of time exposure to benzene fumes. The current study concluded that benzene fumes may have a negative impact on hemoglobin and total serum cholesterol concentration, red and white bloodcells count and lead to decrease of all.